Vascular Pathophysiological Changes in Patients with COVID-19: A Review Article - Mohammad Hassani (Archives of Anesthesia and Critical Care, 2022)
In the last days of 2019, a novel strain of coronaviruses reported in Wuhan and spread rapidly all over the world which called 2019 novel coronavirus (2019- nCoV). Almost a few months later in the early 2020 (January 2020), the WHO declared the outbreak of COVID-19 a Public Health Emergency which Compared with the other SARS- CoV, has a stronger transmission capacity.